Water absorption mechanism and mechanical performance of adhesively joint aluminum alloy with GNP reinforced epoxy - Nurziana, Kong; Nur Zalikha, Khalil (Elsevier Ltd, 2021)
This work investigates the effects of Graphene Nanoplatelets (GNP) reinforcement to water absorption behavior and mechanical properties of adhesively joint aluminum. 1.0 wt% GNP was incorporated into epoxy adhesive to joint aluminum adherend subjected to various immersion periods (10–60 days) for investigating its effect on water uptake, water absorption rate and shear strength. When compared to pristine adhesive, GNP reinforced epoxy exhibit two distinct trends with regard to water uptake and water absorption rate; i) at lower immersion period (10–40 days), increased water uptake and water absorption rate is observed where highest increment recorded are 99.9% and 98.2% respectively at 10 days immersion period, while ii) at longer immersion period (50–60 days) reduced water uptake and water absorption rate is observed where lowest value recorded are 18.4% and 17.9% respectively, at 60 days immersion period. When compared to pristine epoxy, regardless of immersion periods, GNP reinforced specimens have more or less demonstrated retention/deterred joining performance. In this work, it is noted that all fractured specimens with GNP reinforcement demonstrate the combination of both cohesive and adhesive fracture.